Targeting arginine auxotrophy in pancreatic cancer cells using human recombinant arginase I-induced arginine deprivation. (c2017) - Khalil, Nathalie (2017)
Pancreatic cancer (PC) is a highly aggressive solid malignancy with no efficient therapy. It is one of the deadliest cancer types since its mortality rate per year is nearly equal to its incidence rate. Therefore, there’s a need for more effective and selective therapeutic approaches for targeting PC. In this study, we examined the mechanisms of arginine auxotrophy in PC cell lines. Sensitivity to arginine depletion using HuArgI (Co)-PEG5000 was evident in all of the tested PC cell lines with IC50 values in the pM range at 72 hours following treatment. Normal cells, on the other hand, were resistant to HuArgI (Co)-PEG5000-induced arginine deprivation. Sensitivity to HuArgI (Co)- PEG5000-induced arginine deprivation was attributable to the complete dependence on exogenous arginine of two of the five PC cell lines tested and to the partial arginine auxotrophy in combination with fast proliferative requirements of the remaining three cell lines. The lack of ASS-1 expression was demonstrated to be the underlying cause behind complete arginine dependence. It is also important to mention that we noticed an increase in the percent of surviving cells among completely auxotrophic cell lines postaddition of citrulline at 72, 96 and 120 hours of drug incubation. This subpopulation of surviving cells was also determined to be ASS-1 positive hence partially auxotrophic, despite the fact that the cell line was considered overall negative for ASS-1 expression and completely auxotrophic to arginine. This observation underlies the heterogeneity of PC cell lines in terms of ASS-1 expression and auxotrophy to arginine. All the PC cell lines investigated exhibited G0/G1 cell cycle arrest at 72 hours following arginine depletion treatment. Additionally, all five PC cell lines stained negative for annexin V and showed the lack of caspase activation following 24 and 48 hours of arginine deprivation. This absence of caspase activation was confirmed by a 72 hours cytotoxicity assay on Panc-1 cells, which revealed the failure of the pan-caspase inhibitor, Z-VAD, to reverse or decrease arginine depletion-triggered cell death. These findings indicate that HuArgI (Co)-PEG5000-induced arginine depletion results in nonapoptotic, caspase-independent cell death. Additionally, in this study, we are the first to examine the contribution of autophagy following arginine depletion therapy in PC. We have established that autophagy, a process of cellular destruction activated in response to arginine deprivation, can be the leading cause of cell death at late drug incubation times. Hence, our study demonstrates that HuArgI (Co)-PEG5000 is a novel, potent and selective potential therapeutic approach for PC.